Allele frequencies of BRAFV600 mutations in primary melanomas and matched metastases and their relevance for BRAF inhibitor therapy in metastatic melanoma - Satzger, Imke (Oncotarget, 2015)
BACKGROUND: The detection of BRAFV600 mutations in patients with metastatic melanoma is important because of the availability of BRAF inhibitor therapy. However, the clinical relevance of the frequency of BRAFV600 mutant alleles is unclear. PATIENTS AND METHODS: Allele frequencies of BRAFV600 mutations were analyzed by ultra-deep next-generation sequencing in formalin-fixed, paraffin-embedded melanoma tissue (75 primary melanomas and 88 matched metastases). In a second study, pretreatment specimens from 76 patients who received BRAF inhibitors were retrospectively analyzed, and BRAFV600 allele frequencies were correlated with therapeutic results. RESULTS: Thirty-five patients had concordantly BRAF-positive and 36 (48%) patients had concordantly BRAF-negative primary melanomas and matched metastases, and four patients had discordant samples with low allele frequencies (3.4–5.2%). Twenty-six of 35 patients with concordant samples had BRAFV600E mutations, three of whom had additional mutations (V600K in two patients and V600R in one) and nine patients had exclusively non-V600E mutations (V600K in eight patients and V600E -c.1799_1800TG > AA- in one patient). The frequency of mutated BRAFV600 alleles was similar in the primary melanoma and matched metastasis in 27/35 patients, but differed by >3-fold in 8/35 of samples. BRAFV600E allele frequencies in pretreatment tumor specimens were not significantly correlated with treatment outcomes in 76 patients with metastatic melanoma who were treated with BRAF inhibitors. CONCLUSIONS: BRAFV600 mutation status and allele frequency is consistent in the majority of primary melanomas and matched metastases. A small subgroup of patients has double mutations. BRAFV600 allele frequencies are not correlated with the response to BRAF inhibitors.